The Role Of Batulicin Class III Community Institution In Developing Teenage Prisoners Abusing Narcotics - Nila Alda Sari; Ergina Faralita (Interdisciplinary Explorations in Research Journal, 2023)
Abstract The abuse and danger of narcotics is increasing and it cannot be denied that among teenagers and students it can be said to be difficult to overcome. Indonesia is a legal state that provides punishment for perpetrators of violations and crimes, so there are correctional institutions available as a place of guidance and protection for those who are punished for what they have done. The research method used in this research is empirical legal research with a legal sociology approach. The results of the research show that the Batulicin Class III Penitentiary, in cultivating teenage convicts who abuse narcotics, has provided quite good protection, guidance and security for the inmates, even though the security officers and there is not as much guidance as other correctional institutions, but they provide guidance in accordance with Law Number 22 of 2022 concerning Corrections. Keywords : Narcotics, Teenagers, Correctional Institutions Abstrak Penyalahgunaan dan bahaya narkotika semakin meningkat dan tidak bisa di pungkiri di kalangan remaja dan pelajar dapat di katakan sulit untuk di atasi. Negara Indonesia adalah negara hukum yang memberikan hukuman bagi para pelaku pelanggaran dan kejahatan maka tersedianya Lembaga Pemasyarakatan sebagai tempat pembinaan dan perlindungan bagi mereka yang mendapatkan hukuman dari apa yang telah mereka lakukan. Metode penelitian yang digunakan dalam penelitian ini adalah penelitian hukum empiris dengan pendekatan sosiologi hukum.Hasil penelitian menunjukkan bahwa Lembaga Pemasyarakatan Kelas III Batulicin dalam Membina Narapidana Usia Remaja Penyalahgunaan Narkotika sudah memberikan perlindungan, pembinaan dan keamanan yang cukup baik bagi para warga binaan, walaupun petugas penjagaan dan pembinaan belum sebanyak seperti Lembaga Pemayarakatan yang lainnya tetapi mereka memberikan pembinaan yang sesuai dengan Undang-undang Nomor 22 Tahun 2022 tentang Pemasyarakatan. Kata Kunci : Narkotika, Remaja, Lembaga Pemasyarakatan